To Operate or Not to Operate? Reconstructive Surgical Burden and Quality of Life of Pediatric Patients with Facial Differences - Modi, Rishi N.; Blum, Jessica D.; ATASEVEN, BURÇİN; Belza, Caitlyn C.; Montes, Edna; Leung, Karen L.; Zaldana-Flynn, Michelle; Rapoport, Chelsea S.; Choi, Alyssa K.; Ewing, Emily; Malcarne, Vanessa L.; Gosman, Amanda A. (Sage Publications Inc., 2023)
Objective: The Craniofacial Condition Quality of Life Scale (CFC-QoL) was used to evaluate the relationship between surgical burden and quality of life (QoL) Design: Patient-parent dyads completed the CFC-QoL which queries the following QoL domains: Bullying, Peer Problems, Psychological Impact, Family Support, Appearance Satisfaction, and Desire for Appearance Change. Stepwise multivariate linear regressions were performed for each QoL domain. Setting: Urban tertiary care center Patients, participants: Pediatric patients with facial differences, and their parents. Intervention: Survey study Main Outcome Measure(s): Demographic, diagnostic, and surgical characteristics were collected. Surgical burden was calculated as the standard deviation from the mean number of surgeries per diagnostic cohort. Result: Patients (N = 168) were majority female (57.1%) and Hispanic (64.3%). Diagnoses were cleft lip and/or palate (CLP,n = 99) or other craniofacial conditions (CFC,n = 69). Average patient age was 2.3 +/- 5.6 years at first reconstructive surgery and 12.3 +/- 3.4 years at study enrollment. Patients received an average of 4.3 +/- 4.1 reconstructive surgeries. Worse Bullying was associated with higher surgical burden. Worse Peer Problems was associated with higher surgical burden, but only for children with non-CLP CFCs. Worse Family Support was associated with CFC diagnosis, female sex, and higher surgical burden. Worse Psychological Impact was associated with higher surgical burden. Worse Appearance Satisfaction was associated with younger age and with lower surgical burden. Greater Desire for Appearance Change was associated with older age, higher surgical burden, CLP diagnosis, female sex, and non-Hispanic ethnicity. Socioeconomic status did not predict QoL per patient self- or parent-proxy report. Conclusions: Higher surgical burden was associated with worse QoL outcomes in multiple domains.
Keywords: Cleft Lip; Cleft Lip and Palate; Cleft Palate; Nonsyndromic Clefting; Craniosynostosis; Quality of Life; Craniofacial Surgery; Hemifacial Microsomia